Development of Glycaspis brimblecombei Moore (Hemiptera: Aphalaridae) on Eucalyptus camaldulensis Dehnh. and Eucalyptus dunnii Maiden - Cuello, Eliana Marina (2017)
1 The red gum lerp psyllid Glycaspis brimblecombei is an invasive insect species, native from Australia, that specifcally feeds on Eucalyptus trees. It has invaded several countries throughout the world. In Argentina, it was frst recorded in 2005, although little is known about its ecology in the region. 2 We assessed G. brimblecombei population development on Eucalypus camaldulensis and Eucalyptus dunnii using samples of branches for the immature stages and yellow sticky traps for the adults. We also identifed the meteorological variables associated with changes in the red gum lerp psyllid abundance. 3 The abundance of eggs, nymphs and adults stages of G. brimblecombei was signifcantly greater on E. camaldulensis than on E. dunnii in the 2 years of the survey. 4 Glycaspis brimblecombei development was complete on E. camaldulensis where all instars were present, even in the unfavourable seasons. The full development of the psyllid population was not observed in E. dunnii where a high mortality of the frst and second nymphal instars was detected. 5 Temperature and relative humidity were the variables that mostly affected red gum lerp psyllid abundance, whereas no effect of rainfall was detected.